Taylor rules for CEE-EU countries: How much heterogeneity? - Meerim Sydykova; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2015)
We derive Taylor rates for those CEE-EU countries which are not part of the Eurozone. The degree of heterogeneity decreased tremendously over time (2005 - 2015). Nevertheless, the business cycles are still not fully synchronized. As a consequence, joining the Eurozone seems to be premature and should not be an option right now.
Keywords: E52; E58; F15; 330; CEE; monetary policy; currency union; convergence; Taylor rule